2002
DOI: 10.1086/343739
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Specific Prevalence of Infection with Herpes Simplex Virus Types 2 and 1: A Global Review

Abstract: Information on age- and sex-specific prevalence of herpes simplex virus (HSV) types 2 and 1 infections is essential to optimize genital herpes control strategies, which increase in importance because accumulating data indicate that HSV-2 infection may increase acquisition and transmission of human immunodeficiency virus. This review summarizes data from peer-reviewed publications of type-specific HSV seroepidemiologic surveys. HSV-2 prevalence is, in general, highest in Africa and the Americas, lower in wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

58
632
11
30

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 759 publications
(731 citation statements)
references
References 124 publications
58
632
11
30
Order By: Relevance
“…The present data is consistent with other studies that showed evidence of infection with HHVs in the majority of the world's populations [27][28][29][30] .…”
Section: Ethicalsupporting
confidence: 93%
“…The present data is consistent with other studies that showed evidence of infection with HHVs in the majority of the world's populations [27][28][29][30] .…”
Section: Ethicalsupporting
confidence: 93%
“…HSV-1 infection is common, with seropositivity among older adults estimated to be 60-90 % worldwide [39]. A survey from 2005 to 2010 including Americans between 14 and 49 years of age in the USA estimated HSV-1 seropositivity at 54 % and HSV-2 seropositivity at~16 % [40].…”
Section: Epidemiologymentioning
confidence: 99%
“…Thus seropositivity for cytomegalovirus (CMV), Chlamydia pneumoniae (C. pneumoniae), herpes simplex virus 1 (HSV-1), and Helicobacter pylori is greater in individuals of low SES defined by education, poverty or occupational status, and with household crowding [19][20][21][22][23][24][25]. These pathogens are typically acquired in childhood [26], when they may or may not be symptomatic [27][28][29]. Reactivation of specific pathogens such as CMV and HSV-1 may be relevant to disease risk and cognitive decline in older age [30,31].…”
Section: Introductionmentioning
confidence: 99%